2017
DOI: 10.1038/srep40956
|View full text |Cite
|
Sign up to set email alerts
|

The impacts of air pollution on maternal stress during pregnancy

Abstract: To investigate the association of air pollution with maternal stress during pregnancy, we enrolled 1,931 women during mid-to-late pregnancy in Shanghai in 2010. The “Life-Event Scale for Pregnant Women” and “Symptom-Checklist-90-Revised Scale” (SCL-90-R) were used to evaluate life event stress and emotional stress, respectively. Air pollution data were collected for each district where pregnant women lived during pregnancy. We associated ambient air pollution with stress scores using multivariable logistic reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
1
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 47 publications
2
11
1
4
Order By: Relevance
“…(2017) [34] prospective cohort study ozone, PM 2.5 , PM 10 association between both long-term ozone and PM 2.5 exposure and depression onset, specifically stronger with antidepressant use Lin et al (2017) [43] cross-sectional study sulphur dioxide, sarticulate matter dose-dependent association between air pollution and emotional stress during pregnancy Tallon et al (2017) [28] observational, longitudinal, populationbased study PM 2.5 positive associations between recent long-term ambient PM 2.5 levels and erectile dysfunction, depression and stress IJOMEH 2018;31(6) 715 was found that women living in areas with higher levels of NO 2 , PM 10 and SO 2 in addition to increased levels of stress during pregnancy have a higher risk of depressive episodes [43].…”
Section: Ozonementioning
confidence: 99%
“…(2017) [34] prospective cohort study ozone, PM 2.5 , PM 10 association between both long-term ozone and PM 2.5 exposure and depression onset, specifically stronger with antidepressant use Lin et al (2017) [43] cross-sectional study sulphur dioxide, sarticulate matter dose-dependent association between air pollution and emotional stress during pregnancy Tallon et al (2017) [28] observational, longitudinal, populationbased study PM 2.5 positive associations between recent long-term ambient PM 2.5 levels and erectile dysfunction, depression and stress IJOMEH 2018;31(6) 715 was found that women living in areas with higher levels of NO 2 , PM 10 and SO 2 in addition to increased levels of stress during pregnancy have a higher risk of depressive episodes [43].…”
Section: Ozonementioning
confidence: 99%
“…Recent studies suggest that exposure to air pollution during pregnancy may play a role in development of depressive symptoms and postpartum depression ( Niedzwiecki et al., 2020 ; Sheffield et al., 2018 ). One study also has shown an association of exposure to particulate matter from mid to late pregnancy with higher levels of psychological distress during pregnancy ( Lin et al., 2017 ), although they did not find an association specifically with depression. To our knowledge, the association between exposure to air pollution in different trimesters of pregnancy and prenatal depression has not been examined.…”
Section: Introductionmentioning
confidence: 99%
“…Air pollution, as one of the world’s largest health challenges,6 has already been linked to the incidence of human psychological health 7. For example, exposure to air pollution has been found to increase the risk of suicide,8 depression,9 maternal stress,10 autism11 and so on.…”
Section: Introductionmentioning
confidence: 99%